2010
DOI: 10.1111/j.1600-0536.2009.01621.x
|View full text |Cite
|
Sign up to set email alerts
|

The possible relevance of sex hormones on irritant and allergic responses: their importance for skin testing

Abstract: Dermatological responses are affected by the menstrual cycle phase in female patients, an unsurprising observation as oestrogen and progesterone affect the skin and immunological function, with oestrogen suppression of cellular immunity in particular. Exacerbation of dermatological symptoms is typically observed in either the latter phase of the menstrual cycle or during menstruation. The allergic response is diminished in the ovulatory phase and heightened in the progestinic phase. Definitive conclusions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…34,35 We found that 17b-estradiol and progesterone each at a relatively high concentration inhibited the TGF-b2-induced production of IL-6 by cultured mouse RPE cells, with the effect of 17b-estradiol appearing greater than that of progesterone. It is thus possible that 17b-estradiol might prove more effective than progesterone for immunosuppression in the eye.…”
Section: Discussionmentioning
confidence: 93%
“…34,35 We found that 17b-estradiol and progesterone each at a relatively high concentration inhibited the TGF-b2-induced production of IL-6 by cultured mouse RPE cells, with the effect of 17b-estradiol appearing greater than that of progesterone. It is thus possible that 17b-estradiol might prove more effective than progesterone for immunosuppression in the eye.…”
Section: Discussionmentioning
confidence: 93%
“…Nearly half of all patients with atopic eczema experience deterioration in their condition in the week prior to the menstruation, with the exacerbation rapidly settling after the onset of menstrual flow . Skin barrier permeability is greater just prior to menstruation . This increases the susceptibility of skin to the effects of both environmental allergens and general irritants, which partially explains the premenopausal flares of eczema in some women …”
Section: Other Dermatoses Exacerbated By Menstruationmentioning
confidence: 99%
“…Acne vulgaris 4,10 Aphthous ulceration 4,10 Atopic eczema 4,23 Autoimmune progesterone dermatitis 13,14,16,18 Autoimmune oestrogen dermatitis 12 Dermatitis Herpetiformis 4 Erythema multiforme 4 Herpes simplex Oestrogen Progesterone Ovulation Figure 2 Timescale showing when different perimenstrual dermatoses commonly occur during the menstrual cycle, e.g. APD occurs 3-10 days before and 5-10 days after menstruation.…”
Section: Dermatosis Referencesmentioning
confidence: 99%
“…First, estrogens are known to promote skin elasticity and improve wound healing (36). Second, it was reported that skin response to allergens is markedly stronger at follicular phase than during ovulation (37, 38, 39). Third, Bonamonte et al .…”
Section: Discussionmentioning
confidence: 99%